Negotiating Meaning and Authority through Speech Acts: A Pragmatic Study of Arabic Classroom Interaction - Muzakki Abdurrahman; Muhammad Alfa Chirul Murtadho; Sovia Fahraini; Muhammad Thohir (STIQ Amuntai, 2026)
Arabic, as the medium of instruction, plays a central role in fostering communicative interaction between teachers and students. However, differences in linguistic background and communicative competence often pose challenges to effective message delivery and comprehension. In this context, tadāwul af‘āl al-kalām (the exchange of speech acts) serves as a crucial communicative strategy for creating meaningful and effective classroom interactions. This study analyses the forms, functions, and meanings of speech acts in Arabic classroom interaction, as well as their role as a pedagogical communication strategy. A qualitative method with a pragmatic discourse analysis approach was employed, using classroom observation, in-depth interviews, and documentation. Data were thematically analysed based on speech act theory (locutionary, illocutionary, and perlocutionary acts) and functional categories (assertive, directive, expressive, commissive, and declarative). The findings indicate that directive speech acts dominate teacher communication, guiding instructions and learning activities, while students predominantly use assertive speech acts to convey understanding and responses. Expressive and commissive speech acts also emerge in affective and collaborative contexts. These results underscore that speech acts are not merely tools for information delivery but adaptive strategies that foster participatory, reflective, and meaningful classroom interaction. The pedagogical use of af‘āl al-kalām has the potential to strengthen students’ communicative competence and enhance the quality of Arabic language learning.